Foreign residency rights and companies' auditor choice - Xue Yang; Zhi Jin; Jinsong Tan (China Journal of Accounting Research, 2019)
Recently, with the migration of wealthy Chinese elites becoming increasingly prevalent, the market has come to believe that firms with controlling persons with foreign residency rights have serious agency problems. We study the impact of controlling persons with foreign residency rights on corporate audit perspective. We find that firms whose controlling persons have foreign residency rights are more likely to use high-quality auditing services, and that this behavior is more obvious in regions with lower marketization and in firms with higher separation of ownership and control. We further study the effect of firms whose controlling persons have foreign residency rights that use high-quality Big 4 auditors and find that such firms have better corporate governance and accounting performance.
Keywords: 650; Audit; Corporate governance; Foreign residency rights; Signal transmission